Pembelajaran Berbasis Peserta Didik Dengan Menggunakan Media Poster Terhadap Peningkatan Kemampuan Membaca Bahasa Jepang Pada Siswa Kelas XI Bahasa SMAN 113 Jakarta - Wulan Uswatun Hasanah; Rita Agustina Karnawati (Diponegoro University, 2022)
Student Centered Learning, or hereinafter abbreviated as SCL, is present as a solution to the problem of incompatibility of Teacher Centered Learning learning methods. SCL emphasizes the student-centered learning process, where in this approach, students become active actors in learning activities. The presence of the student-centered learning method is expected to be able to improve the quality and learning abilities of school students. This study aims to determine the effectiveness of learning Japanese with poster media to improve the Japanese reading ability of students in class XI Language at SMAN 113 Jakarta. The research method is student-based learning with the research design being Pre-Experimental Design with the One-Group Pretest-Posttest Design model. The study included 40 students from SMAN 113 Jakarta's class XI Language.Data analysis in the study was carried out in several stages, namely the validity test, reliability test, homogeneity test, normality test, t test, and n gain score. The findings revealed that there was a substantial effect or difference in student-based learning using poster media on enhancing Japanese language acquisition reading ability when compared to before treatment. The N Gain Score test, which uses two statistics, the mean and median, shows that the strategy is extremely effective in developing Japanese language abilities.